Diversity and interaction network of mites on agri-horticulture crops of selected areas of West Bengal in India - Soumi Ghosh; Salil Kumar Gupta; Pushan Chakraborty; Indrani Chakraborty (Persian Journal of Acarology)
The South 24 Parganas district of West Bengal, India is very rich in the cultivation of agri-horticultural crops, but nowadays the crop production yield is declining due to the attack of phytophagous mites. A survey was undertaken in selected localities of the South 24 Parganas to understand the diversity of mite fauna associated with agri-horticultural crops. A network approach was applied to determine some of the mite-plant network parameters such as specialization and nestedness. The present paper deals with a total of 39 species of plant mites (18 phytophagous, 19 predatory, and two fungal feeding groups) belonging to 19 genera and 10 families. The majority of the plants on which these mites were recorded formed new host/habitat records. Brevipalpus rica, Tetranychus ludeni, and T. macfarlanei were found important injurious mites, while Amblyseius largoensis and Paraphytoseius bhadrakaliensis were found abundantly as predators and had biocontrol importance. The study also showed that the phytophagous mites had greater sample diversity compared to predatory mites. The network analysis of mite-plant association revealed that mites form a highly specialized and less nested network with host plants. It was also observed that in this network, Phaseolus vulgaris has a mite hub-like role having high centrality values. This study may form a baseline of acarological studies in South Bengal area, which might be helpful in designing pest management strategies.